Diagnostic outcomes for genetic testing of 70 genes in 8565 patients with epilepsy and neurodevelopmental disorders. (14th April 2018) - Lindy, Amanda S.; Stosser, Mary Beth; Butler, Elizabeth; Downtain‐Pickersgill, Courtney; Shanmugham, Anita; Retterer, Kyle; Brandt, Tracy; Richard, Gabriele; McKnight, Dianalee A.
Summary: Objective: We evaluated >8500 consecutive, unselected patients with epilepsy and neurodevelopmental disorders who underwent multigene panel testing to determine the average age at molecular diagnosis and diagnostic yield of 70 genes. Methods: We reviewed molecular test results for 70 genes known to cause epilepsy and neurodevelopmental disorders using next generation sequencing (NGS) and exon‐level array comparative genomic hybridization (aCGH). A positive result was defined as the presence of 1 or 2 pathogenic or likely pathogenic (P/LP) variants in a single gene, depending on the mode of inheritance of the associated disorder. Results: Overall, 22 genes were found to have a high yield of positive findings by genetic testing, with SCN1A and KCNQ2 accounting for the greatest number of positive findings. In contrast, there were no positive findings in 16 genes. Most of the P/LP variants were sequence changes identified by NGS (90.9%), whereas ~9% were gross deletions or duplications detected by exon‐level aCGH. The mean age of molecular diagnosis for the cohort was 5 years, 8 months (ranging from 1 week to 47 years). Recurrent P/LP variants were observed in 14 distinct genes, most commonly in MECP2, KCNQ2, SCN1A, SCN2A, STXBP1, and PRRT2 . Parental testing was performed in >30% of positive cases. All variants identified in CDKL5, STXBP1, SCN8A, GABRA1, and FOXG1 were de novo, whereas 85.7% of variants in PRRT2 were inherited. Significance: Using a combined approach of NGS and exon‐level aCGH, testing identified a genetic etiology in 15.4% of patients in this cohort and revealed the age at molecular diagnosis for patients. Our study highlights both high‐ and low‐yield genes associated with epilepsy and neurodevelopmental disorders, indicating which genes may be considered for molecular diagnostic testing.